EJBM 2020
DOI: 10.7176/ejbm/12-5-10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Firm's Age, Size and Growth on Its Profitability: Evidence from Jordan

Abstract: This study aims at testing the effect firm's age, size and growth on its profitability based on the financial data of (22) Jordanian insurance firms that are registered in the Amman Security Exchange (ASE) during the period (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017). They represent 95.2 % of insurance firms. The study relied on secondary data of insurance firms that have been published on their website and on ASE website In the study, the mean, standard deviations were used to describe the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Therefore, the larger the company size, the more positive signals it can provide. The results of this research support the research of Rahman and Yilun [28], Al Nawaiseh [29] and Kartiningsih and Daryanto [30], who stated that company size has a significant positive influence on the company's Return On Assets (ROA). b.…”
Section: Hypothesis Test Results and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, the larger the company size, the more positive signals it can provide. The results of this research support the research of Rahman and Yilun [28], Al Nawaiseh [29] and Kartiningsih and Daryanto [30], who stated that company size has a significant positive influence on the company's Return On Assets (ROA). b.…”
Section: Hypothesis Test Results and Discussionsupporting
confidence: 87%
“…Rahman and Yilun [28]; Al Nawaiseh [29]; Kartiningsih and Daryanto [30] revealed that company size has a positive effect on profitability. This statement means that the profitability will also increase if the company's size grows.…”
Section: The Effect Of Company Size On Profitabilitymentioning
confidence: 99%
“…However, these studies did not clarify which internal factors have the most significant effect on a firm's profitability (Škuflć et al, 2016). Nevertheless, few previous studies have been conducted on emerging markets, testing the effect of internal factors on profitability for more than one industry, and this also includes the Jordanian context (e.g., Bhayami, 2010; Malik, 2011; Jaber & Al-khawaldeh, 2014; Pratheepan, 2014; Kaddumi & Ramadan, 2012;Al-Nawaiseh, 2020). To the best of the authors' knowledge, investigating the effect of internal factors on a firm's profitability for all listed firms and all types of industries within the corporate sector has not been examined before in Jordan.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that Firm Chaecteristic has an insignificant effect on Financial Performance, is corroborated by past studies done by Megawati and Dermawan (2019) in their research stated that firm age has an insignificant effect on firm performance. Nawaiseh (2020) in his research stated that there was an insignificant effect of company age and company size on profitability. The findings of this study indicate that the age and size of the company is not a guarantee that the company will have Dian Ferriswara, Okta Karneli, Bibi Noraini Mohd Yusuf (2024) good performance.…”
Section: Discussionmentioning
confidence: 99%